Afghanistan Development Update, October 2015 - World Bank (Washington, DC, 2015)
More frequent incidences of violence in Afghanistan, as well as delays in the elections process and cabinet formation, continued to fuel uncertainty and affected investor confidence in 2014 and the first half of 2015. Economic growth slowed to 1.3 percent in 2014, down from 3.7 percent a year earlier. Unlike in previous years, agriculture did not contribute much to growth in 2014. Production levels were high for a third year in a row but did not supersede the strong output in 2013. Growth was mainly driven by services and a slight expansion of industries where an increase in construction activities outweighed lower production in manufacturing. Private investment activities showed strong signs of slowdown in 2014, evidenced by a drop of nearly 50 percent in new firm registrations since 2012. The National Unity Government has embarked on an ambitious reform agenda to revitalize the economy, tackle corruption, and improve investment climate. However, it will take time for these reforms to have an impact, and it is yet unclear how much they will mitigate the high risks stemming from the fragile security environment. Growing trends in security and pension and wage spending over the medium term require immediate attention. Afghanistan faces significant financing shortages for both civilian and security spending. Therefore, securing continued high levels of donor financing over the coming years is of critical importance for fiscal stability in the country. The fragile security environment and financing constraints, compounded by weak governance capacity, pose serious challenges to service delivery in Afghanistan. Any setback in reform implementation would further slowdown the pace of human capital accumulation in Afghanistan and reduce future prospects of growth and poverty reduction.